Pregunta
upstudy study bank question image url

Solve for \( u \). \[ 3+\frac{1}{u+6}=-\frac{5}{(u+1)(u+6)} \] If there is more than one solution, separate them with commas. If there is no solution, click on "No solution". \( u=\square \square \)

Ask by Beck Mann. in the United States
Feb 27,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( u = -\frac{4}{3} \)

Solución

To solve the equation   3 + 1/(u + 6) = -5/((u + 1)(u + 6)), we first note that u ≠ -6 and u ≠ -1 (to avoid division by zero). Step 1. Multiply both sides of the equation by (u + 1)(u + 6) (valid since u avoids -1 and -6):   3(u + 1)(u + 6) + (u + 1) = -5. Step 2. Expand (u + 1)(u + 6):   (u + 1)(u + 6) = u² + 7u + 6. Substitute back:   3(u² + 7u + 6) + (u + 1) = -5. Step 3. Expand and combine like terms:   3u² + 21u + 18 + u + 1 = 3u² + 22u + 19. So, we have:   3u² + 22u + 19 = -5. Step 4. Bring -5 to the left side:   3u² + 22u + 19 + 5 = 3u² + 22u + 24 = 0. Step 5. Solve the quadratic equation 3u² + 22u + 24 = 0. Calculate the discriminant:   D = 22² - 4·3·24 = 484 - 288 = 196, and √D = 14. Step 6. Use the quadratic formula:   u = (-22 ± 14) / (2·3). This gives two potential solutions:   u = (-22 + 14) / 6 = (-8) / 6 = -4/3,   u = (-22 - 14) / 6 = (-36) / 6 = -6. Step 7. Reject any extraneous solutions: Since u = -6 makes a denominator zero in the original equation, we must discard it. Thus, the valid solution is:   u = -4/3.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To solve the equation \[ 3+\frac{1}{u+6}=-\frac{5}{(u+1)(u+6)}, \] we'll first eliminate the fractions by multiplying both sides by \( (u+1)(u+6) \): \[ 3(u+1)(u+6) + (u+1) = -5. \] This expands to: \[ 3(u^2 + 7u + 6) + (u + 1) = -5. \] Distributing the 3 yields: \[ 3u^2 + 21u + 18 + u + 1 = -5. \] Combine the like terms: \[ 3u^2 + 22u + 19 = -5. \] Now, add 5 to both sides: \[ 3u^2 + 22u + 24 = 0. \] Next, we can use the quadratic formula: \[ u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{-22 \pm \sqrt{22^2 - 4 \cdot 3 \cdot 24}}{2 \cdot 3}. \] Calculating the discriminant: \[ 22^2 = 484, \] and \[ 4 \cdot 3 \cdot 24 = 288. \] So the discriminant is: \[ 484 - 288 = 196. \] Now, taking the square root gives: \[ \sqrt{196} = 14. \] Now substituting back into the formula: \[ u = \frac{-22 \pm 14}{6}. \] Calculating the two possibilities for \( u \): 1. For \( u = \frac{-22 + 14}{6} = \frac{-8}{6} = -\frac{4}{3} \). 2. For \( u = \frac{-22 - 14}{6} = \frac{-36}{6} = -6 \). Thus, the solutions are: \[ u = -\frac{4}{3}, -6. \] Therefore, the final answer is: \( u = -\frac{4}{3}, -6 \)

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad